Influence of viral and host characteristics on clinical outcome of hepatitis B / Chook Jack Bee - Chook, Jack Bee (2013)
Hepatitis B is a global health problem, affecting >2 billion people worldwide. Chronicity develops in >90% of neonates infected by hepatitis B virus (HBV). After several decades of the infection, about a-quarter-to-half may progress to liver cirrhosis and hepatocellular carcinoma (HCC). In contrast, more than 90% of people infected during adulthood may clear the infection, resulting in acute self-limiting hepatitis. Both virus and host may influence clinical outcome of the infection. Basal core promoter (BCP; A1762T/G1764A) and precore stop codon (G1896A) mutations have been commonly associated with cirrhosis and HCC, whereas wild-types of these mutations with acute hepatitis. These associations have been inconsistent; the disease progression may have been affected by other non-viral factors. Host iron status could be one of the important factors; iron overload increases risk of cirrhosis and HCC. It has rarely been considered in chronic hepatitis B studies. The present study is divided into two sections. The aim of the first section is to investigate the influence of viral genomic variations and host iron markers (serum iron and serum ferritin) on progression to cirrhosis and HCC, whereas the second section to identify potential viral genomic variations associated with chronicity based on in silico observation. Overlapping polymerase chain reaction (PCR) was applied to amplify viral genomic fragments. The fragments were then sequenced and assembled. Sera were also sent to clinical laboratory for testing of the iron markers. To search for candidate nucleotides associated with cirrhosis, comparative sequence analysis was performed in 20 cirrhotic cases and 20 controls, whereas for HCC, the analysis was done in 21 HCC cases and 24 controls. The most potential viral marker was then applied in larger chronic hepatitis B populations, including 216 controls, 78 cirrhosis and 39 HCC cases. Binary logistic regression analysis showed that older age, cigarette smoking, family history of cirrhosis/HCC, HBV precore wild-type, serum iron and serum ferritin were associated independently iv with HCC, whereas older age, male gender, Malay ethnicity, precore wild-type, serum iron and serum alanine aminotransferase (ALT) with cirrhosis. To search for candidate nucleotides associated with chronicity, comparative sequence analysis was conducted in 177 acute cases and 1,149 chronic cases. Binary logistic regression coupled with Bonferroni-correction identified four novel viral variants (G1171, T1785, A1786 and T3112) independently associated with acute hepatitis. These variants are located in enhancer-I-X-promoter and S promoter regions, mutations in which result in reduced viral replication and release. In conclusions, older age, precore wild-type and serum iron markers may increase the risk of progression to cirrhosis and HCC, but not to NAFLD. Cigarette smoking, male gender, Malay ethnicity and high serum ALT should also be considered. The present study has also identified novel variants (G1171, T1785, A1786 and T3112) highly specific for acute self-limited infection. These putatively replicationdefective variants may be responsible for lower rate of chronicity in some cases of HBV infection. Further in vitro and in vivo investigations are required to confirm this hypothesis.